Teaching Programming Experiences in Times of COVID-19 in the State of Zacatecas - Lara, Elvia; Garcia, Josefina; Minero, J Jesus (2021 10th International Conference On Software Process Improvement (CIMPS), 2021)
The COVID-19 pandemic has caused the suspension of face-to-face classes; therefore, greater importance has been given to virtual education. For this reason, it is important to review the new situations in the programming teaching process. This paper aims to interpret the experiences lived by teachers in in the subjects of Fundamentals of Programming and Data Structure in the implementation of virtual education in times of COVID-19 in the Technological Institutes Decentralized from the State of Zacatecas, for this reason, the quantitative, non-experimental research was used. The instrument used was a digital survey addressed to teachers from the Technological Institutes. According to the results obtained, the main problems during virtual education were the lack of connection by geographical location and the lack of adaptation to virtual education. Teaching virtual programming was a good pedagogical experience, the teachers expressed that they gave personalized attention in small groups; however, they mentioned that it was difficult to measure the student's progress, and the subject contents were not seen with the required degree of complexity. For teaching programming, teachers used platforms such as Moodle, Classroom and Microsoft Teams, virtual classrooms such as Meet and Zoom and digital resources such as videos, presentations and practical manuals. The most important challenges are to have the infrastructure required for the implementation of virtual classes, and the responsibility, commitment and initiative by teachers and students.